2018
DOI: 10.1016/j.resuscitation.2018.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal cardiopulmonary resuscitation for cardiac arrest: A systematic review

Abstract: There is inconclusive evidence to either support or refute the use of ECPR for OHCA and IHCA in adults and children. The quality of evidence across studies is very low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
144
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(158 citation statements)
references
References 51 publications
1
144
0
10
Order By: Relevance
“…Some reports have shown good outcomes from extracorporeal circulation during CPR but, overall, the evidence of benefit is scarce and limited by the observational nature of the studies. 68 Extracorporeal circulation during CPR may help carefully selected patients, but balance must be achieved between efficient resource use and clinical benefits.…”
Section: Resultsmentioning
confidence: 99%
“…Some reports have shown good outcomes from extracorporeal circulation during CPR but, overall, the evidence of benefit is scarce and limited by the observational nature of the studies. 68 Extracorporeal circulation during CPR may help carefully selected patients, but balance must be achieved between efficient resource use and clinical benefits.…”
Section: Resultsmentioning
confidence: 99%
“…42 Fortunately, five ongoing randomized controlled trials will hopefully fill this knowledge gap in the upcoming years. 20 Third, the longterm effects of complications of ECPR should be investigated, since they could decrease the cost-effectiveness of the intervention. The knowledge gained from further research could improve implementation and cost-effectiveness of this costly and labour-intensive intervention.…”
Section: Discussionmentioning
confidence: 99%
“…16 Although evidence from randomized controlled trials is lacking, 17 observational studies have repeatedly shown an increase in survival after ECPR compared to conventional CPR. [18][19][20] Furthermore, the American Heart association recommends the in-hospital use of ECPR in patients with a reversible cause of CA (e.g. : acute coronary syndrome).…”
Section: Introductionmentioning
confidence: 99%
“…However, if done in settings with the appropriate resources utilizing an aggressive strategy with optimum patient selection, survival can possibly be favorable [14]. However, evidence remains inconclusive and requires further study [66].…”
Section: Special Mention: Out-of-hospital Ecprmentioning
confidence: 99%